Dissection of transcriptional and cis‐regulatory control of differentiation in human pancreatic cancer. (14th January 2016) - Diaferia, Giuseppe R; Balestrieri, Chiara; Prosperini, Elena; Nicoli, Paola; Spaggiari, Paola; Zerbi, Alessandro; Natoli, Gioacchino
Abstract: The histological grade of carcinomas describes the ability of tumor cells to organize in differentiated epithelial structures and has prognostic and therapeutic impact. Here, we show that differential usage of the genomic repertoire of transcriptional enhancers leads to grade‐specific gene expression programs in human pancreatic ductal adenocarcinoma (PDAC). By integrating gene expression profiling, epigenomic footprinting, and loss‐of‐function experiments in PDAC cell lines of different grade, we identified the repertoires of enhancers specific to high‐ and low‐grade PDACs and the cognate set of transcription factors acting to maintain their activity. Among the candidate regulators of PDAC differentiation, KLF5 was selectively expressed in pre‐neoplastic lesions and low‐grade primary PDACs and cell lines, where it maintained the acetylation of grade‐specific enhancers, the expression of epithelial genes such as keratins and mucins, and the ability to organize glandular epithelia in xenografts. The identification of the transcription factors controlling differentiation in PDACs will help clarify the molecular bases of its heterogeneity and progression. Synopsis: By combining expression profiling, epigenomic footprinting and loss‐of‐function experiments, this work catalogues the differential usage of transcription factors and enhancers during tumor progression in human pancreatic ductal adenocarcinoma (PDAC). Carcinomas show various degrees of histological deviation from the tissue they derive from (tumor grade). Pancreatic ductal adenocarcinomas (PDACs) show great intra‐tumor grade heterogeneity, which determines a different sensitivity of cells of the same tumor to therapeutic agents. The transcriptional and cis ‐regulatory determinants of human low‐ and high‐grade PDACs were dissected through a combination of epigenomic, transcriptomic and genetic approaches. Transcription factors and genomic regulatory sequences controlling differentiation of human PDACs were identified and validated. Among them, KLF5 contributes to controlling the epithelial program and is required for the recruitment to cis ‐regulatory elements of other transcription factors selectively expressed in low‐grade PDACs. Abstract : By combining expression profiling, epigenomic footprinting and loss‐of‐function experiments, this work catalogues the differential usage of transcription factors and enhancers during tumor progression in human pancreatic ductal adenocarcinoma (PDAC).